2008
DOI: 10.2183/pjab.84.386
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-390 is the binding site of luminous substance with symplectin, a photoprotein from Okinawan squid, Symplectoteuthis oualaniensis

Abstract: Symplectin is a photoprotein from a luminous squid, Symplectoteuthis oualaniensis. It has a luminous substrate, dehydrocoelenterazine (DCZ), linked through a thioether bond with a cysteine residue. We have proven the binding site of luminous substrate in symplectin by using an artificial analogue of DCZ, ortho-fluoro-DCZ (F-DCZ). F-DCZsymplectin emitting strong blue light was reconstituted from apo-symplectin and F-DCZ. Proteolytic digestion of the reconstituted F-DCZ-symplectin afforded peptides including C 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…35 Besides these applications, fluorinated-analog has been playing important roles to elucidate the molecular mechanism of the bioluminescence of symplectin photoprotein. 22 Many important syntheses of coelenterazine 1 and its analogs have been reported by several research groups including ours. However, most of the synthetic routes are focused on either modifying the aryl group on the 2-position (R 1 ) or introducing only limited diversified groups at the 6-position (R 2 ) and the 8-position (R 3 ) starting from 2-aminopyrazine analogs as shown in Scheme 2.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…35 Besides these applications, fluorinated-analog has been playing important roles to elucidate the molecular mechanism of the bioluminescence of symplectin photoprotein. 22 Many important syntheses of coelenterazine 1 and its analogs have been reported by several research groups including ours. However, most of the synthetic routes are focused on either modifying the aryl group on the 2-position (R 1 ) or introducing only limited diversified groups at the 6-position (R 2 ) and the 8-position (R 3 ) starting from 2-aminopyrazine analogs as shown in Scheme 2.…”
Section: Introductionmentioning
confidence: 88%
“…20e22 In 2008, the active center cysteine was determined to be 390-Cys in the 501 amino acids of symplectin. 22 Recently, Kuse independently reported that a commercially available photoprotein pholasin, from Pholas dactylus, showed an increase in the bioluminescence by addition of DCL. 23 Synthesis of coelenterazine or dehydrocoelenterazine has been well established since 1990 until recent 2009.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro assay for light emission detection. The method to confirm light emission in vitro was adapted from previous methodologies that studied the photoproteins Aequorin and Symplectin (1,(12)(13)(14). The standard light emission assay consisted of the addition of 50 lL of either the crude extract of photophores or a chromatographic fraction whose activity was being tested for light emission, and diluting this in 940 lL Tris-HCl buffer (pH 8.5, 50 mM, 0.4 M NaCl).…”
Section: Methodsmentioning
confidence: 99%
“…15) Symplectin has eleven cysteines on its amino acid sequence. 16) One of the residues of cysteines was therefore postulated to form the chromophore for the luminescence of symplectin. The structure of the chromophore was then investigated especially focusing on the carbon atom which was bound to the sulfhydryl residue at the active site of symplectin.…”
Section: )mentioning
confidence: 99%
“…3). 15,16) During these analyses, the most active DCL analog (2,4-diF-DCL) was prepared. The 2,4-difluoro-DCL was then utilized to analyze the stereochemistry of the chromophore.…”
Section: )mentioning
confidence: 99%